Perencanaan Sistem Antrian untuk Penentuan Jumlah Loket Penimbangan yang Optimal dengan Metode Simulasi - Mujahidin, M Laksono (Jurnal Teknik Industri, 2008)
PG Kebon Agung is a goods company which product is sugar. In case of regulating queue of truck loaded with sugar tree, this company is suggested to do it properly. This time it still take for very long time for the truck loaded with sugar tree to be processed later. Long time queue can cause decreasing sugar product quality. PG Kebon Agung hasn’t been able to overcome this problem, so it’s necessary a method to decrease direct and indirect cost for public service supplying due to large number of truck waiting to served. If supplying service facility is not optimally, it’ll cause delayed service, therefore applying queue simulation model is right management system to reduce the queue. By using Arena Software 3.0, the most optimal service chose by PGKA is by using 3 loket penimbangans, because by using 3 loket penimbangans the number of truck in the system, from waiting to finishing process is 5.8333 trucks a minutes. By using more than 3 loket penimbangans it will decrease more queue but the loket penimbangan s have more standby and cost a lot of money.